Designing the Virtual SPIKEY-20 Epidemic. - Strawhacker, Amanda.; Kafai, Yasmin.; T. Giang, Michael.; Fields, Deborah.; Tofel-Grehl, Colby. (Tufts University. Tisch Library., 2023)
Keywords: Public health practices, Virtual epidemics, Virtual worlds.; ACM Open.